Inquiry into the cultural impact on cost accounting systems (CAS) in Sri Lanka. Issue 4 (4th April 2017) - Nagirikandalage, Padmi; Binsardi, Ben
Abstract : Purpose: The purpose of this paper is to critically explore the implementation of cost accounting systems (CAS) using content analysis. In particular, it aims to examine the impact of Sri Lankan cultural and local characteristics on the adoption of CAS. In particular, it examines the factors that facilitate or hinder the adoption of CAS in Sri Lanka. Design/methodology/approach: Primary data for the research were obtained by interviewing selected respondents from Sri Lanka's manufacturing and service sectors. They were shortlisted using maximum variation sampling to obtain a representative cross-section of the national population. A total of 16 respondents were interviewed, which resulted in 57 interview paragraphs to be coded. Several theories were used to analyse them, namely, the theory of institutional isomorphism (homogeneity) and the theory of heterogeneity, as well as Clifford Geertz's cultural theories. Findings: A cross-comparison between the findings and relevant literature indicates the existence of complete institutional isomorphism and partial institutional heterogeneity in Sri Lanka. Heterogeneity exists in organisations such as foreign multinationals, which have adopted unique and sophisticated CAS. In addition, inadequate access to information and the orientation of the local culture has affected the implementation of CAS in Sri Lanka, with a lack of awareness of the importance of CAS, a sluggish approach to costing and cultural values forming prominent barriers to its implementation. These findings are plausible in light of the relationship between a sluggish approach towards costing (a low cost awareness), and local attitudes towards the implementation of more efficient accounting practices such as CAS. Practical implications: This research is invaluable as a tool for Sri Lankan policymakers and practitioners, enabling the public and private sectors to provide education and training to enhance staff understanding and promote a positive attitude towards costing. With more efficient institutional CAS, the country's economy will be more competitive internationally. As well as policymakers and practitioners, this research could be used by academicians for advancing theoretical development around the cultural triggers and barriers for adopting more innovative and fresher CAS in Sri Lanka. Originality/value: The originality of this research can be justified on two counts. Firstly, although a wealth of research exists that examines the influence of culture on behaviour, this research specifically evaluates the impact of cultural factors on attitudes towards costing. These factors could be facilitators or obstructions for implementing CAS. Secondly, this research aims to combine both earlier and recent theories of institutionalism with Clifford Geertz's cultural theory, to investigate how people and institutions in Sri Lanka adopt CAS. Earlier studies have focused merely on earlier theories of institutional homogeneity.